Layout Design by Comparing Dedicated Storage Method and Class-Based Storage Method of Spare Parts Warehouse at Phthalic Anhydride (PA) Company - Syarifudin Arifin, Mohammad; Andesta, Denny (Fakultas Sains dan Teknologi Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
A warehouse is a fixed facility or building that can store goods, raw materials, and finished materials used during production. Therefore, an effective warehouse layout design can help smooth production and storage processes. PT XYZ is a company that produces Phthalic Anhydride (PA). The company has a spare parts warehouse that stores materials, such as mechanical spare parts, electrical spare parts, chemicals, and consumables. The company's problem is that the storage layout's design is not organized, and the materials are not neatly arranged, so it takes time to search and ignore the types of fast-moving and slow-moving materials. Therefore, the purpose of this research is to redesign the layout of the company's warehouse to make it more efficient. The implementation of this research uses a comparison of 2 methods to choose the most optimal one to use, namely dedicated storage and class-based storage. The dedicated Storage method is used as fixed storage because the material place has been determined. In contrast, class-based storage is a method of grouping goods according to each group's type, size, and block boundaries. The results of the calculation of dedicated storage amounted to 472.75m. In comparison, the results of the calculation of class-based storage showed a total jar of 498.1m with an initial layout distance of 529.75m. Then, the most optimal layout proposal uses a dedicated storage layout proposal. Based on the implementation of the research, the benefits obtained from using this method are shortening the retrieval distance and making it easier for employees to find materials. Keywords: warehouse, layout, design, dedicated storage, class-based storage